Penerapan Strategi Pemasaran, Inovasi Produk Dan Orientasi Pasar Untuk Meningkatkan Kinerja Pemasaran Umkm Sektor Olahan Keripik Di Kabupaten Gresik, Provinsi Jawa Timur - Nailul Fawaid; Nur Hidayati; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The creation of a new marketing strategy cannot be separated from innovation, both advertising innovation and product innovation, both products that have been implemented and the discovery of new products, so that the products made by MSME players in Gresik Regency must be able to supply new products, products that are different and much better than competitors' products.This study uses quantitative research methods and the type of research conducted uses explanatory research. With a quantitative approach, namely an approach to testing the hypothesis using numerical calculations through statistical techniques, this research uses non-probability sampling techniques and the population in this study are all MSMEs in the Chips Processed sector in Gresik Regency, totaling 97 MSMEs Processed Chips in Gersik Regency. The variables of Marketing Strategy, Product Innovation, and Market Orientation simultaneously affect the marketing performance of MSMEs Processed Chips in Gresik Regency. Market Strategy has a partial effect on the marketing performance of MSMEs Processed Chips in Gresik Regency. Product innovation variables have a partial effect on the marketing performance of Kripik Processed MSMEs in Gresik Regency. And Product Quality has a partial effect on the marketing performance of Kripik Processed MSMEs in Gresik Regency. Keywords: Market Orientation, Marketing Strategy, and MSMEs